THE RELATIONSHIP BETWEEN GADGET USE AND SOCIAL DEVELOPMENT EMOTIONAL BEHAVIOR OF SCHOOL-AGE CHILDREN AT SDN 3 MINDAHAN - Ahsanu Nadya Zidni Ilma; Indanah; Anny Rosiana Masithoh (PT. Radja Intercontinental Publishing, 2026)
The increasing use of gadgets among school-aged children raises concerns about their social-emotional development, particularly regarding their ability to interact socially, manage emotions, and behave prosocially. This study aims to analyze the relationship between gadget use and the social-emotional development of school-aged children at SDN 3 Mindahan, Batealit District, Jepara Regency. This study used a quantitative approach with a cross-sectional design. Sampling was conducted using a total sampling technique, so that the entire population of 119 students was used as the research sample. Data collection was carried out using a gadget use questionnaire and the Strengths and Difficulties Questionnaire (SDQ). Data analysis included univariate and bivariate analysis using the Spearman's Rho test. The results showed that 48% of respondents had low gadget use, 43% had moderate use, and 9% had high use. Most children had normal social-emotional development (90%). There was a significant relationship between gadget use and social-emotional development on the difficulty scale (p=0.000; r=0.559) with a positive direction and moderate strength. Furthermore, there was a significant negative correlation between gadget use and social-emotional development on the strength scale (p=0.010; r=-0.256). The study concluded that higher gadget use led to higher levels of social-emotional difficulties and lower prosocial behavior in school-aged children.